2008
DOI: 10.1016/j.expneurol.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of paratrigeminal nociceptive neurons following temporomandibular joint inflammation in rats

Abstract: To evaluate the involvement of paratrigeminal nucleus (Pa5) nociceptive neurons in temporomandibular joint (TMJ) inflammation-induced pain and its autonomic correlates, we conducted behavioral, single unit recording and Fos immunohistochemical studies in anesthetized rats. Nocifensive behaviors to mechanical, heat or cold stimulation of the lateral face over the TMJ region were significantly enhanced in the TMJ-inflamed rats for 10–14 days after injection of complete Freund’s adjuvant (CFA) into the TMJ and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…Similar to the response at caudal Vc, TMJ-evoked Fos-LI at the dPa5 increased with greater stimulus intensity, was mainly ipsilateral to the stimulus and was enhanced by high estrogen conditions (Bereiter 2001; Okamoto et al 2008). Lesion of the dPa5 prevented cardiovascular reflex responses to noxious stimuli (Yu et al 2002), while recording studies found that dPa5 neurons encoded facial skin stimulus intensity and became sensitized after TMJ injury (Yamazaki et al 2008). Although the dPa5 likely is critical for somatic autonomic integration in the trigeminal system (Saxon and Hopkins 1998; Caous et al 2001), these studies were performed in male animals, and thus, it is not known if sex differences influence the contribution of dPa5 to TMJ nociceptive processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the response at caudal Vc, TMJ-evoked Fos-LI at the dPa5 increased with greater stimulus intensity, was mainly ipsilateral to the stimulus and was enhanced by high estrogen conditions (Bereiter 2001; Okamoto et al 2008). Lesion of the dPa5 prevented cardiovascular reflex responses to noxious stimuli (Yu et al 2002), while recording studies found that dPa5 neurons encoded facial skin stimulus intensity and became sensitized after TMJ injury (Yamazaki et al 2008). Although the dPa5 likely is critical for somatic autonomic integration in the trigeminal system (Saxon and Hopkins 1998; Caous et al 2001), these studies were performed in male animals, and thus, it is not known if sex differences influence the contribution of dPa5 to TMJ nociceptive processing.…”
Section: Discussionmentioning
confidence: 99%
“…C-fos immunohistochemical studies have confirmed that select regions of the TBNC that receive direct input from the TMJ, e.g., dorsal paratrigeminal region (dPa5) and superficial laminae of Vc and upper cervical dorsal horn (C 1–2 ), encode the intensity of an intra-TMJ stimulus in an estrogen-dependent manner (Bereiter 2001; Okamoto et al 2008). Anatomical tract-tracing combined with c-fos methods have been used to report that TBNC neurons responsive to jaw muscle (Ikeda et al 2003; Sugiyo et al 2005) or TMJ injury (Yamazaki et al 2008) projected to higher brain centers associated with nociceptive processing; however, only male animals were included in these studies.…”
mentioning
confidence: 99%
“…Despite observing similar TMJ-evoked responses of units in naïve and CFA-treated rats prior to PD98059 application, the effectiveness of PD98059 on TMJ unit activity was markedly enhanced 2 weeks after CFA. Although testing at 2 weeks after intra-TMJ injection of CFA has confirmed ongoing behavioral hyperalgesia (Yamazaki et al, 2008), the exact role of TMJ units in superficial laminae at the Vc/C 1–2 region in mediating changes in behavior is not yet known. Others have claimed that elevated E2 has an antihyperalgesic or even analgesic effect on TMJ-related behavior (Fischer et al, 2008; Kramer and Bellinger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular administration of Complete Freund’s Adjuvant (CFA) is a well-established animal model for monoarthritis that causes persistent joint inflammation (Wilson et al 2006) and long-term changes nociceptive behavior in rodents (Butler et al 1992; Schadrack et al 1999; Luo et al 2008). In male rats intra-TMJ injection of CFA produces orofacial cutaneous hyperalgesia lasting at least 2 weeks (Imbe et al, 2001; Okamoto et al, 2005a; Yamazaki et al, 2008) and increases the expression of pERK-positive neurons in Vc after jaw movement at that time (Suzuki et al, 2007). In cycling female rats, we found that 2 weeks after CFA treatment the number of Fos-positive neurons produced at the Vc/C 1–2 region after TMJ stimulation was enhanced in proestrous (high E2) compared to diestrous (low E2) female rats suggesting a role for sex hormone status in TMJ-evoked responses during chronic inflammation (Bereiter et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, NADPH-d stained neurons were mainly concentrated in the Vc, Pa5 and DMSp5. Pa5 are thought to be involved in processing trigeminal nociceptive information (Yamazaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%